Origins of the Segmental Arteries in the Aorta: An Anatomic Study for Selective Catheterization with Spinal Arteriography - Shimizu, Satoru; Tanaka, Ryusui; Kan, Shinichi; Suzuki, Sachio; Kurata, Akira; Fujii, Kiyotaka (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: The segmental arteries, which include the posterior intercostal, subcostal, and lumbar arteries, are gateways for performance of selective spinal arteriography of the thoracolumbar level. We performed a cadaveric study to clarify the anatomic relationship between the origins of the segmental arteries in the aorta and the vertebral column.METHODS: Five adult cadaveric aortas with intact thoracolumbar spines were dissected under magnification. In each specimen, nine pairs of posterior intercostal arteries, one pair of subcostal arteries, and four pairs of lumbar arteries were examined in detail.RESULTS: The origin of the posterior intercostal arteries in the upper thoracic level was situated at most about two levels caudal to the feeding level, whereas the origins in the lower levels were just caudal to the corresponding levels. The position of the bilateral orifices of the segmental arteries in the axial plane of the aorta was on the medial side at the thoracic levels, whereas it was on the dorsal side at the lumbar level. The horizontal distance between the orifices in the lumen of aorta was found to be wider at the thoracic level than the lumbar level, and the longitudinal distance was higher at the lower level, corresponding to the height of the vertebra.CONCLUSION: Understanding the 3D relationship of the initial segment of the segmental arteries with reference to the aorta and vertebral column is necessary for performance of the selective spinal arteriographic examination rationally by using a two-dimensional fluorescent display.